Cholinergic Modulation of Type 2 Immune Responses - Bosmans, Goele; Shimizu Bassi, Gabriel; Florens, Morgane; Gonzalez-Dominguez, Erika; Matteoli, Gianluca; Boeckxstaens, Guy E. (Frontiers in Immunology, 2017)
In recent years, the bidirectional relationship between the nervous and immune system has become increasingly clear and its role in both homeostasis and inflammation has been well documented over the years. Since the introduction of the cholinergic anti-inflammatory pathway, there has been an increased interest in parasympathetic regulation of both innate and adaptive immune responses, including Th2 responses. Increasing evidence has been emerging suggesting a role for the parasympathetic nervous system in the pathophysiology of allergic diseases, including allergic rhinitis, asthma, food allergy and atopic dermatitis. In this review, we will highlight the role of cholinergic modulation by both nicotinic and muscarinic receptors in several key aspects of the allergic inflammatory response, including barrier function, innate and adaptive immune responses, and effector cells responses. A better understanding of these cholinergic processes mediating key aspects of type 2 immune disorders might lead to novel therapeutic approaches to treat allergic diseases.